Whataboutism: genesis and examples in media - Zadworny, Patryk (Zjawiska propagandy i manipulacji w prasie, telewizji, radiu i Internecie, 2022)
Whataboutism, also known as whatabouttery, is a variation of tu quoque sophism that attempts to discredit an opponent's position by accusing them of hypocrisy without directly refuting their arguments. According to Russian writer, chess grandmaster and political activist Garry Kasparov, whataboutism is a word that was coined to describe the frequent use of rhetorical diversion by Soviet apologists and dictators to refute allegations of their oppression, "massacres, gulags and forced deportations," by invoking American slavery, racism, lynchings, etc. Whataboutism has also been used by other politicians and state governments. Whataboutism is particularly associated with Soviet and Russian propaganda. When the Soviet Union was criticized during the Cold War, the response often used the style of "what about you?" by citing an event or situation in the Western Word.